1992
DOI: 10.18174/njas.v40i4.16504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pattern of water supply on Vicia faba L. 4. Simulation studies on yield variability.

Abstract: The effects of water supply patterns on yield variability of Vicia faba L. were studied by means of a crop growth model. The model simulates crop dry matter production and soil water availability in dependence on plant characteristics and weather and soil data. Conse quences of various weather conditions on growth were evaluated, using 4 data sets from various soils and sites in Western Europe. In set 1 (14 years; heavy clay soil; Netherlands) and set 3 (2 years; 9 locations in Western Europe), linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Except for one spring type, the slope of days to flower vs. daylength was the same for all types, but the types differed in the apparent intercept to the longest daylength at which rate of development was most rapid (range was 12 h for spring type to more than 24 h for the slowest winter type). We concluded that there is a wide array of faba bean types such that degree‐day–oriented coefficients without daylength sensitivity may work for spring types in Germany (Stutzel, 1995a, 1995b) and the Netherlands (Grashoff and Stokkers, 1992) but not for winter types grown in France, Spain, and the Mediterranean. Evans (1957) found evidence of vernalization in the winter types; however, this was the only reference in the literature.…”
Section: Resultsmentioning
confidence: 91%
“…Except for one spring type, the slope of days to flower vs. daylength was the same for all types, but the types differed in the apparent intercept to the longest daylength at which rate of development was most rapid (range was 12 h for spring type to more than 24 h for the slowest winter type). We concluded that there is a wide array of faba bean types such that degree‐day–oriented coefficients without daylength sensitivity may work for spring types in Germany (Stutzel, 1995a, 1995b) and the Netherlands (Grashoff and Stokkers, 1992) but not for winter types grown in France, Spain, and the Mediterranean. Evans (1957) found evidence of vernalization in the winter types; however, this was the only reference in the literature.…”
Section: Resultsmentioning
confidence: 91%